2011
DOI: 10.1038/msb.2011.38
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of mRNA and protein and integration with protein turnover in a bacterium

Abstract: Determination of the average cellular copy number of 400 proteins under different growth conditions and integration with protein turnover and absolute mRNA levels reveals the dynamics of protein expression in the genome-reduced bacterium Mycoplasma pneumoniae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
295
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(318 citation statements)
references
References 55 publications
20
295
2
1
Order By: Relevance
“…Both coefficients were used in previous studies to calculate mRNAprotein relationships (for review, see Maier et al, 2009;Vogel and Marcotte, 2012). In general, the relationship between mRNA and protein abundance is considered positive in a wide range of organisms but varies greatly between the studies (yeast [Lee et al, 2011], bacteria [Maier et al, 2011], maize endosperm and embryos [Walley et al, 2013], and maize leaf sections [Ponnala et al, 2014]). Variations in mRNAprotein correlation might be explained by many factors, such as bias in RNA and protein stability and movement, experimental measurement, and quantification methods (Ponnala et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Both coefficients were used in previous studies to calculate mRNAprotein relationships (for review, see Maier et al, 2009;Vogel and Marcotte, 2012). In general, the relationship between mRNA and protein abundance is considered positive in a wide range of organisms but varies greatly between the studies (yeast [Lee et al, 2011], bacteria [Maier et al, 2011], maize endosperm and embryos [Walley et al, 2013], and maize leaf sections [Ponnala et al, 2014]). Variations in mRNAprotein correlation might be explained by many factors, such as bias in RNA and protein stability and movement, experimental measurement, and quantification methods (Ponnala et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics studies from various organisms have shown a very poor, slightly positive correlation between mRNA levels and protein abundance (Taniguchi et al, 2010;Maier et al, 2011;Schwanhäusser et al, 2011;Vogel and Marcotte, 2012). Additionally, it is clear that many proteins are under posttranslational control, and we do not currently know to what extent posttranslational modifications (such as phosphorylation) play a role in UPS-mediated processes in plants.…”
Section: Future Directionsmentioning
confidence: 99%
“…Transcriptomics and proteomics technologies both provide important and complementary insights: The former allow researchers to generate global quantitative gene expression profiles and to study gene regulatory aspects like the impact of short RNAs. However, due to the varying correlation of transcriptomics and proteomics data reported in the literature (de Godoy et al 2008;de Sousa Abreu et al 2009;Maier et al 2011;Marguerat et al 2012), the direct measurement of protein expression levels is often desirable. For certain aspects, proteomics data can provide more informative and accurate data, as it reflects the effects of other important regulatory processes like protein translation rates and protein stability (Schwanhausser et al 2011).…”
mentioning
confidence: 99%